Episode two: India’s policy pathways - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2024)
In this second installment of our new podcast, our host Chhavi Sachdev takes you to her home country of India to explore the nuanced policy landscape of the world’s most populous country. Chhavi is joined by an insightful range of guests: CGIAR Initiative on National Policies and Strategies’ lead author for India’s policy coherence report, Archisman Mitra, Senior Program Lead at Council on Energy, Environment and Water (CEEW), Nitin Bassi, and Research and Advocacy team coordinator at Professional Assistance for Development Action (PRADAN), Parijat Ghosh. Together they address Indian Policy Coherence, the challenges, and the proposed solutions for the sustainable development of food, land, and water systems.